Impact of the COVID-19 Pandemic on the Diagnosis of Tuberculosis in Brazil: Is the WHO End TB Strategy at Risk? - Souza, Mariana do Rosário; Paz, Wandklebson Silva da; Sales, Vinícius Barbosa dos Santos; Jesus, Gleidson Felipe Hilario de; Tavares, Débora dos Santos; Lima, Shirley V. M. Almeida; Sousa, Álvaro Francisco Lopes; Melo, Enaldo Vieira de; Carmo, Rodrigo Feliciano do; Souza, Carlos Dornels Freire de; Bezerra-Santos, Márcio (Frontiers in Pharmacology, 2022)
Background: In 2014, the World Health Organization (WHO) launched the "post-2015 End TB strategy", that aims to end the global tuberculosis (TB) epidemic by 2030. However, the COVID-19 pandemic has severely impacted global public health and the strict measures to control the coronavirus spread can affect the management of other diseases, such as TB. Herein, we aimed to assess the impact of the COVID-19 pandemic on the diagnosis of TB in Brazil, during 2020. Methods: We carried out an ecological and population-based study, using spatial analysis techniques. The variables used were the new cases of TB, pulmonary tuberculosis (PTB), and also baciloscopy-positive (BP) cases in Brazil between 2015 and 2020. The percentage of changes (% change) was calculated to verify if there was an increase or decrease of TB cases in 2020, along with time trend analyses given by Joinpoint regression model. Also, interrupted time series analyses were used to assess the trend of TB diagnosis before and after the onset of the COVID-19 in Brazil. Spatial distribution maps were elaborated, considering the % change of each Brazilian state. Findings: Data analyses showed a reduction in the diagnosis of TB (-8.3%) and PTB (-8.1%) in Brazil after the irruption of the COVID-19 pandemic. Likewise, 22 states depicted a reduction in TB diagnosis. An expressive reduction of BP cases (-17.1%) was also observed. Interestingly, interrupted time series analysis showed decline in TB and PTB diagnoses from March 2020. Spatial analyses revealed that all states had a progressive reduction of TB, PTB and PB cases, from March on, with the highest percentages of reduction in December (-100% to -75%). Interpretation: Taken together, our analyses demonstrated a reduction in TB diagnosis after the irruption of the COVID-19 pandemic in Brazil and its regions, signaling a serious impact on the WHO “End TB Strategy” global plan.